Facile access to α-acyloxyamides via epoxide rearrangement/three-component domino reaction catalyzed by indium(III) chloride. Issue 15 (2nd August 2016) - Lingaswamy, Kadari; Krishna, Palakodety Radha; Prapurna, Y. Lakshmi
ABSTRACT: A simple and efficient Passerini reaction of epoxides involving highly regioselective rearrangement of epoxide to aldehyde/three-component Passerini reaction catalyzed by indium(III) chloride is described. In the present protocol, epoxides served as wonderful substrates to furnish a library ofα -acyloxyamides under mild reaction conditions in shorter reaction times and in good yields. GRAPHICAL ABSTRACT: